SINODE DAN PENOLAKAN PRIVATISASI PANTAI PEDE - Inosentius Mansur (Jurnal Alternatif Wacana Ilmiah Interkultural, 2016)
One of important points of Synod III dioses of Ruteng is to refuse the privatization of Pede Beach by enterpreneur. It's the reasonable decision.Pede Beach is the only one of public space that so far could be accessed by public freely. The government of NTT province that has the property of rights of Pede Beach enstruted the third party to manage Pede Beach. In this case, PT Sarana Investama Menggabar (SIM) of Setya Novanto is the party that will get the big benefit.Itseems, Memoranduum of Understanding (MoU)between NTT province and PT SIM has dealt the 25 years ofcontract byPT SIM in managing Pede Beach. Of course, it will increse the capitalization of public space on the coastal area of Labuan Bajo. It means, in just a little while the indegenous of Manggarai Barat will be "ata bana" (the staranger) in their land. The will be excluded from their area of existence. Synod as legal reprsentative and aspirative forum is impossible keeping silent in facing this public space problem. Synod insists the government of province to give the management of Pede Beach to Manggarai Barat Regency.The synod wants the good management of beach as the public space, in whic the people can express themself as the recreative human. Inosentius Mansur,through this article wants to discover our eyes of heart in placing the Pede Beach not only in tourism economyside. More than that, Pede Beach must be placed as the symbol of'selfdignity' of Manggarai Barat's people. So, the management of Pede Beach by enterpreneur that marginalize the local society is not worth to do.